2018
DOI: 10.3892/ijmm.2018.3546
|View full text |Cite
|
Sign up to set email alerts
|

An adenosine�A1R-A2aR imbalance regulates low glucose/hypoxia-induced microglial activation, thereby contributing to oligodendrocyte damage through NF-κB and CREB phosphorylation

Abstract: Microglial activation-mediated inflammatory damage to oligodendrocytes is a key step in the etiology of ischemic white matter lesions. The adenosine A1 receptor (A1R) and adenosine A2a receptor (A2aR) have been reported to regulate the activation of microglia, however, the underlying mechanisms remain elusive. Thus, the present study used a microglia/oligodendrocyte co‑culture model exposed to low glucose/hypoxia, and treated with agonists/antagonists of A1R and A2aR to investigate the role of A1R and A2aR. Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…58,59 The regulation of NF-κB is crucial for the expression of iNOS and MCT1 in pro-inflammatory microglia. [60][61][62][63] However, the relationship between MCT1 and iNOS in stroke models has not been explored before. Here, knocking down MCT1 significantly reduces the expression of iNOS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…58,59 The regulation of NF-κB is crucial for the expression of iNOS and MCT1 in pro-inflammatory microglia. [60][61][62][63] However, the relationship between MCT1 and iNOS in stroke models has not been explored before. Here, knocking down MCT1 significantly reduces the expression of iNOS.…”
Section: Discussionmentioning
confidence: 99%
“…The regulation of NF‐κB is crucial for the expression of iNOS and MCT1 in pro‐inflammatory microglia 60–63 . However, the relationship between MCT1 and iNOS in stroke models has not been explored before.…”
Section: Discussionmentioning
confidence: 99%
“…We used a group of rats treated with CGS 21680 (an A2AR agonist) to investigate the effects of XYS on A2AR signaling in the striatum. Previous studies have suggested that A2AR serves an important role in the onset of microglial activation and inflammation after exposure to a low glucose/hypoxia in a NF-κB-dependent manner ( Huang et al, 2018 ). We found that intraperitoneal injection of CGS 21680 can also activate the A2AR-ERK-NF-κB pathway in the striatum and induce a depression-like phenotype, which was reversed by treatment with XYS.…”
Section: Discussionmentioning
confidence: 99%
“…After 1 week of adaptation, the rats in the MS group and MSX group were treated with the A2AR antagonist SCH 58261, and the rats in the CC group and CCX group were treated with the A2AR agonist CGS 21680. The dosages were 0.05 mg/kg·d and 0.1 mg/kg·d, respectively ( Pan and Chen, 2007 ; Costenla et al, 2011 ; Kaster et al, 2015 ; Huang et al, 2018 ). The rats in the other groups were given the same amount of 0.9% NS.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, under ischemia, it is possible that lactate, another monocarboxylate, is taken up by the highly expressed MCT1 and converted to pyruvate for use in the mitochondria. NF-κB is vital in low glucose-induced microglial activation [51] and for iNOS [52,53] and MCT1 [54] expressions. But, the relationship between MCT1 and iNOS has not been explored.…”
Section: Discussionmentioning
confidence: 99%